Vaginal Tablets of Metronidazole (750 mg) plus Miconazole Nitrate (200 mg) versus Oral Metronidazole (2 g) for Bacterial Vaginosis: A Randomized Controlled Trial - Thamkhantho, Manopchai; Chayachinda, Chenchit; Lertaroonchai, Chanita (Siriraj Medical Journal, 2021)
Objective: To compare the cure rates, side effects, satisfaction, and recurrence rates of bacterial vaginosis (BV) in women having vaginal tablets of metronidazole (750 mg) plus miconazole (200 mg)—the “NPF group”—versus oral metronidazole (2 g)—the “MET group.” Materials and methods: This September 2019–March 2020 trial enrolled symptomatic women aged 18–45 years diagnosed with BV based on Amsel’s criteria. Excluded were women who were immunocompromised; allergic to metronidazole or miconazole; had BV episodes during the preceding 3 months; or had abnormal vaginal bleeding. After randomization with a ratio 1:1, another vaginal swab was done for Nugent scoring. Two weeks later, the evaluation using Amsel’s criteria and Nugent scores was repeated. Also, symptom resolution, side effects and satisfaction were evaluated. Symptomatic resolution referred to 75% improvement in discharge, irritation, itching, odor, and coital pain. At one and three months, subjective symptomatic recurrence was assessed by telephone. Results: Data on 70 participants were analyzed (NPF, N=34; MET, N=36). Their average age was 32.3±7.9 years (NPF, 34.1±8.1; MET, 30.6±7.3). Without statistical significance, NPF had higher symptom resolution (67.7% vs 58.3%; P=0.420), cure rate by Amsel criteria (82.4% vs 77.8%; P=0.632), and cure rate by Nugent scoring (35.3% vs 16.9%; P=0.075). Both groups reported high satisfaction (NPF, 8.5±1.4; MET, 7.9±2.0; P=0.125). Side effects were comparable, including appetite loss, metallic taste, nausea, and dizziness. Conclusion: For BV treatment, both vaginal ovules containing metronidazole (750 mg) plus miconazole nitrate (200 mg) and oral metronidazole (2 g) show comparable efficacy and side effects.